A dinâmica da dívida publica no Brasil entre 1995 e 2010 - Santos, Eduardo José dos (2013)
Have in view to crescent retaking of the theme of the public debt, mainly due to the aggravation of the Greek crisis and in other countries of the European Union, causing impacts of global proportions, the present paper intends to analyze the behavior of the Brazilian public debt among the years of 1995 and 2010, not just observing their respective starting points and arrival, but what took it, which varied were decisive and the government's reason to have taken this direction in the administration of the public debt, being verified during this period there were points of apparent explosion of the public debt, what took to these points and which attitudes taken on the part of the government did with that this returned to a maintainable path. For so much, we will firstly to consider what the public debt is, the reason why it happens and which are their impacts in the economy, and for the analysis of the impacts we will present different concerning approaches to the subject. Soon afterwards we will stated the main by means of the financing of public debt, detailing the impacts for each mentioned mechanism, finally in this I surrender will present the theoretical and practical concept of the sustainability of the public debt, presenting, besides, the mathematical model that will be used in the evaluation of the sustainability of the public debt in elapsing of the work. In the sequence the work analyzes the evolution of the public titles in the period from 1995 to 2010, will verify like this that the alteration of the profile of the emissions of the government's titles along the analyzed period contributed positively to the credibility and sustainability of the debt. Like this the work will make, in the sequence, the analysis of the dynamics of the public debt between 1995 and 2010, verifying that this, in spite of having if enlarged considerably during the analyzed period, it transmits a superior fiscal condition to observed her in I begin it of the period, leaning in the macroeconomics and fiscal results due to the stabilization of the economy and improvement of the administration of the public debt